Potential cutaneous hypersensitivity reaction to an inactive ingredient of thyroid hormone supplements in a dog. Issue 1 (21st December 2015) - Lavergne, Sidonie N.; Fosset, Fabrice T.J.; Kennedy, Peter; Refsal, Kent R.
Abstract : Background: Although discussions about allergic reactions to thyroid supplements abound on professional forums, there is almost no information in the literature on these specific idiosyncratic drug reactions. Animal: A dog with a history of hypothyroidism‐associated weight gain and mild lethargy was prescribed levothyroxine tablets (0.018 mg/kg twice daily). After 19 days the dog developed a severe skin condition that was responsive to levothyroxine withdrawal, and antibiotic and glucocorticoid therapy. Three weeks later a different levothyroxine tablet was prescribed. Within 48 h the dog developed a more severe cutaneous reaction that resolved with drug discontinuation and appropriate topical care. Objectives: To confirm a possible hypersensitivity reaction and identify its chemical target. Methods and results: The two prescribed levothyroxine formulations shared two inactive ingredients: magnesium stearate and polyvinylpyrrolidone. Nine months after discontinuation of thyroid supplement, a formulation without either of these two compounds was used for a second re‐challenge. There was no recurrence of the drug reaction and after 1.5 years of treatment the dog remains normal. Conclusions and clinical importance: These elements strongly suggest that this dog had an idiosyncratic reaction (likely immune‐mediated) against one or both inactive ingredients in the first two formulations of levothyroxine. We are not aware of any previous confirmed delayed hypersensitivity to a thyroid supplement in a dog with the likely chemical trigger being an inactive ingredient rather than the therapeutic agent itself. We hope that this case will raise awareness about allergic reactions to thyroid supplements and allergic reactions to inactive formulation components. Abstract : Background –Although discussions about allergic reactions to thyroid supplements abound on professional forums, there is almost no information in the literature on these specific idiosyncratic drug reactions.Objectives –To confirm a possible hypersensitivity reaction and identify its chemical target.Conclusions and clinical importance –These elements strongly suggest that this dog had an idiosyncratic reaction (likely immune‐mediated) against one or both inactive ingredients in the first two formulations of levothyroxine. We are not aware of any previous confirmed delayed hypersensitivity to a thyroid supplement in a dog with the likely chemical trigger being an inactive ingredient rather than the therapeutic agent itself. We hope that this case will raise awareness about allergic reactions to thyroid supplements and allergic reactions to inactive formulation components.